2008
DOI: 10.1111/j.1475-4991.2008.00269.x
|View full text |Cite
|
Sign up to set email alerts
|

Poverty Dynamics During Trade Reform: Evidence From Rural Vietnam

Abstract: This paper implements and adapts the conceptual framework developed by Winters (2002) that identifies the transmission mechanisms between trade policy reform and household welfare outcomes. We make use of household panel data from Vietnam collected in two years, 1992-93 and 1997-98 that span the very earliest years of the reform period and its immediate after effects. Poverty dynamics are modeled using changes in consumption expenditure and poverty transition models. The trade effect is captured by a set of va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
2
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(26 citation statements)
references
References 37 publications
(64 reference statements)
2
18
2
2
Order By: Relevance
“…We observe that welfare does not discriminate against living in a female headed household, which is consistent with findings from some developing country studies (e.g. Appleton, 1996;Justino et al, 2008) but contrary to results from others (e.g. Finan et al, 2005;Kijima and Gonzalez, 2013;Mensah et al, 2014).…”
Section: Welfare Effects Of Transient Livelihood Diversitysupporting
confidence: 77%
See 2 more Smart Citations
“…We observe that welfare does not discriminate against living in a female headed household, which is consistent with findings from some developing country studies (e.g. Appleton, 1996;Justino et al, 2008) but contrary to results from others (e.g. Finan et al, 2005;Kijima and Gonzalez, 2013;Mensah et al, 2014).…”
Section: Welfare Effects Of Transient Livelihood Diversitysupporting
confidence: 77%
“…For example, a household whose head completed secondary or higher education has, on average, 18 percent higher consumption than a household whose head has no formal education. Our estimate is comparably larger than the 8 percent reported by Justino et al (2008) for Vietnamese household panel data but considerably lower than that reported by Ackah et al (2014) who used nationally representative data from Ghana but employed income as the welfare measure. In addition to the positive welfare effect of head's education, having an educated spouse in the household significantly contributes to consumption welfare gains.…”
Section: Welfare Effects Of Transient Livelihood Diversitycontrasting
confidence: 72%
See 1 more Smart Citation
“…This approach was used by other transitions studies (Glewwe et al 2002;Niimi et al 2004Niimi et al , 2007Justino et al 2008).…”
Section: Datamentioning
confidence: 99%
“…Los cambios estructurales tienen diferentes efectos según las condiciones de cada país. Así, las reformas asociadas a la liberalización del comercio pueden convertirse en una política contra la pobreza y una estrategia de desarrollo (Winters et al, 2004), tener efectos positivos en los hogares rurales pobres a través del mercado de trabajo (Justino et al, 2008), o por el contrario, ofrecer oportunidades de acumulación y éxito para agricultores de mediana y gran escala, mientras los de pequeña buscan alternativas a la agricultura o se condenan a reducir los niveles de productividad (Oya, 2001).…”
Section: Introductionunclassified